Digitalization of the Quick Response Indonesian Standard (QRIS) Payment System for MSME Development - Dewi Qutrun Nada; Sri Suryaningsum; Hari Kusuma Satria Negara (AIBPM Publisher, 2021)
Digitalization of payment systems in the business world is a certainty at this time. This paper is an initial literature review that will discuss the use of server-based e-commerce, the discussion will present QRIS (Quick Response Code Indonesian Standard), the readiness of MSMEs in using information technology, the application of QRIS on MSMEs, QRIS constraints on MSMEs. This paper is important because the need to use server-based e-commerce is already one of the most popular cashless payment systems. Server-based e-commerce format is e-wallet or digital wallet. This paper is important because it examines the role of regulators and standards in the use of QRIS (QR Code Indonesian Standard). The use of QRIS helps to standardize QR code systems. This research attempts to examine the application of QRIS to MSMEs in terms of the role, limitations, and income of MSMEs with QRIS. The research method used is by tracing literature that uses QRIS as a payment method for the character. This study shows that QRIS offers benefits for MSME traders.